Exploring feedback dynamics: an experimental analysis of human and computer feedback on motivation, engagement, and GRIT in secondary school students - Heindl, Lizzy; Huber, Veronika; Schuricht, Victoria; Wawrzinek, David; Babl, Ulrich; Ellert, Guido (Frontiers in Education, 2025)
This study explored the impact of different feedback forms on the psychological parameters of learning success: motivation, engagement, and GRIT (GRIT: Growth, Resilience, Integrity, and Tenacity, a concept introduced to describe perseverance and passion for long-term goals) among 6th and 7th-grade students at secondary schools in Bavaria, Germany, employing a 2 × 3 factorial design. The factors included the type of feedback (human-based vs. computer-based), and the declaration of feedback type (grades/points anonymously vs. social comparison/group feedback vs. Pass/NoPass). Among 219 students, findings showed human-based feedback significantly improved feedback evaluations, while computer-based feedback notably increased GRIT. Additionally, feedback in the form of Pass/NoPass and social comparison positively affected GRIT. No significant impacts on motivation or engagement were detected. The results highlight the importance of tailored feedback strategies in fostering GRIT, though they suggest limited generalizability.